Defoliating Insect Mass Outbreak Affects Soil N Fluxes and Tree N Nutrition in Scots Pine Forests - Grüning, Maren M.; Simon, Judy; Rennenberg, Heinz; l-M-Arnold, Anne (Frontiers in Plant Science, 2017)
Biotic stress by mass outbreaks of defoliating pest insects does not only affect tree performance by reducing its photosynthetic capacity, but also changes N cycling in the soil of forest ecosystems. However, how insect induced defoliation affects soil N fluxes and, in turn, tree N nutrition is not well studied. In the present study, we quantified N input and output fluxes via dry matter input, throughfall, and soil leachates. Furthermore, we investigated the effects of mass insect herbivory on tree N acquisition (i.e. organic and inorganic 15N net uptake capacity of fine roots) as well as N pools in fine roots and needles in a Scots pine (Pinus sylvestris L.) forest over an entire vegetation period. Plots were either infested by the nun moth (Lymantria monacha L.) or served as controls. Our results show an increased N input by insect feces, litter and throughfall at the infested plots compared to controls, as well as increased leaching of nitrate. However, the additional N input into the soil did not increase, but reduce inorganic and organic net N uptake capacity of Scots pine roots. N pools in the fine roots and needles of infested trees showed an accumulation of total N, amino acid-N, protein-N, and structural N in the roots and the remaining needles as a compensatory response triggered by defoliation. Thus, although soil N availability was increased via surplus N input, trees did not respond with an increased N acquisition, but rather invested resources into defense by accumulation of amino acid-N and protein-N as a survival strategy.